INCREASING THE EFFICIENCY OF TEACHING THROUGH THE APPLICATION OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
The topic of this scientific work is “Increasing the effectiveness of teaching through the use of innovative pedagogical technologies in the educational process”. The main objective of the study is to study the theoretical and practical aspects of the use of modern pedagogical technologies in the educational process, to determine their impact on students' learning activities, independent thinking and motivation for learning. The research used pedagogical observation, comparison, questionnaire survey, interview and experimental testing methods. The results showed that the use of interactive methods and information and communication technologies increases the activity of students, helps to better assimilate knowledge and significantly improves the effectiveness of teaching.
Keywords: Innovative pedagogy; pedagogical technologies; interactive methods